Modifications cytophysiologiques induites par la procaine chez quelques plantes aquatiques marines - Cosma, Dorina Căchiță; Știrban, M.; Iordan, Margareta; Bercea, V. (Cercetări Marine - Recherches Marines, 2026)
Concentration of 1ppm hydrochloride of procaine in the life medium of the aquatic plants Enteromorpha intestinalis, Cladophora sp. and Zostera nana have determined an action of stimulating the activity of citocromoxidase and peroxidase, of the accumulation of Ca and P, and also an increase of the content in chlorophyll a and carotenoidic pigments. The concentration of 100ppm caused negative changes which increased as the duration of the treatment extended.